TOKOH AJI SAKA PERSPEKTIF IDEOLOGI DAN TEOLOGI - Putu Marria Ratih Anggraini; I Nyoman Suka Ardyasa (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
The character of Aji Saka cannot be separated from the forerunner of the Javanese and Balinese script. In various mythologies, the character Aji Saka is a central figure in the birth of the Balinese script. The story of Aji Saka is one of the myths encountered by Balinese people in ancient times and still exists today. Furthermore, the mythology of Aji Saka tells of a prabhu named Aji Saka as the main character, who comes from India (Hindustan). His arrival in the archipelago was not just for creating Javanese and Balinese characters. But in fact, it is a reflection of the influence of Hindu culture from the land of India which finally reached the archipelago. So there is an element of civilization in it. The ideology of Aji Saka, who has the idea of teaching Hinduism to the entire community in Medang Kemulan, Aji Saka's thought is very visionary in building mankind and protecting weak communities. Aji Saka is also reflected as a figure who is smart and able to give confidence to his servants who in the end is able to create the Javanese and Balinese script that we have inherited to this day. In the context of theology, the figure of Aji Saka is related to Indian civilization that entered the archipelago, especially for the Hindu community in Bali, the second is that the philosophy of script wreastra is a way to unite with Ida Sang Hyang Widhi Wasa.